Topicality of the problem of combined course of multi-drug resistant pulmonary tuberculosis with diabetes mellitus - O. M. Raznatovska; Yu. M. Bobrovnycha-Dvizova; S. B. Norejko; N. A. Gricova (Zaporozhye State Medical University, 2017)
According to the World Health Organization, today in the world among the infectious chronic diseases one of the leading places and causes of death is multi-drug resistant tuberculosis of the lungs, and chronic non-communicable diseases - diabetes mellitus. The situation is complicated by the fact that the number of patients with combined course of these two heavy separate illnesses that complicate each other increases. It is established that with increasing severity of diabetes mellitus, tuberculosis process in the lungs becomes more complicate and deteriorates, and vice versa, the specific process complicates the course of diabetes mellitus, contributing to the development of diabetic complications. Against this background, the effectiveness of treatment of patients suffering from multi-drug resistant tuberculosis of the lungs in our country remains very low, mainly due to the toxic adverse reactions to antimycobacterial drugs of the reserve line, and in the case of adding diabetes mellitus, it deteriorates even more. The aim of this study was to review the scientific literature to determine the relevance of the study of combined course of multi-drug resistant tuberculosis of the lungs with diabetes mellitus and perspectives of innovative methods of diagnosis of diabetes mellitus. Early diagnosis of pre-diabetes, and autoimmune diseases will allow the use of timely correction techniques that prevents the development of diabetes mellitus, depending on its type, and in the future the development of serious irreversible processes, allow timely applying appropriate methods of correction of the revealed violations. Results. Very little amount of work is dedicated to the problem of combined course of multi-drug resistant tuberculosis of the lungs with diabetes mellitus, regardless of its type, the theme is relevant for today, in Ukraine there are no data regarding its study. This combined course of very difficult in the treatment diseases requires not only timely and early diagnosis of autoimmune diseases associated with diabetes mellitus type 1 and pre-diabetes, but also additional complex combined therapy.